A cidade, o lazer e a criança: o Programa Curumim no Sesc/Santana (2005 a 2014) - Teixeira, Alexandre Francisco Silva (2015)
This research aims to explore leisure in urban daily life on the North Side of São Paulo. It refers to the Cultural and Sports Centre implemented by Serviço Social do Comércio do Estado de São Paulo (SESC/SP) named SESC/Santana. In order to achieve results about SESC/SP's strategy for socio-educational leisure, project "Curumim Program" was chosen, especially considering that this project has been lead since the inauguration of SESC/Santana. The choice of this theme is based on the fact that leisure in São Paulo is a subject scarcely studied academically. The working method adopted was based on the analysis of images, reports, videos, interviews and specialized bibliography about leisure produced by SESC/SP. Such historical sources clarified that the strategy used by the SESC reveals an unique way to organize time/space for leisure